ANALISIS KESTABILAN TITIK KESETIMBANGAN MODEL MATEMATIKA PROSES TRANSMISI VIRUS DENGUE DI DALAM TUBUH MANUSIA DENGAN TERAPI OBAT HERBAL - Juliah, Intan; Supriyono, Supriyono (Unnes Journal of Mathematics, 2016)
Dengue fever is an infectious diseese caused by the dengue virus. Dengue virus in to the human body through the intermediary of A. Aegypti mosquito bites. In the human body, the virus uses the cell as a medium to poliferate and survive. The presence of viruses in the human body activates the immune respone is T-cell to inhibit the breeding of dengue virus takes too medicinal plants. In this article, the transmission of dengue virus in the human body modeled mathematically, the next will be determined the stability of the equilibrium point of the model. Result of analysis showed that the stability of the equilibrium point of dengue virus depends on the basic reproduction ratio (R0). If R0 < 1 then the equlibrium point is virus free local asymptotically stable, whereas if R0 > 1 then the equilibrium point is endemic will be asymptotically stable local